Analysis of Translation Techniques in the Film Fall in Love at First Time - Jessy; Pasaribu, New Millenium (Journal of Language Development and Linguistics, 2023)
The aim of this research is to describe the translation techniques in the film subtitle "Yī wěn dìng qíng《一吻定情》: fall in love at first kiss" and to describe the translation techniques that are more often used in the film subtitle "Yī wěn dìng qíng" 《一吻定情》: fall in love at first kiss based on the translation technique developed by Molina and Albir. The research method used in this research is a descriptive qualitative research method. Based on the research results, it shows that there are 14 translation techniques out of 193 techniques used in translating the film Fall in Love at First Kiss. Based on the results of research analysis, the translation technique in the film Fall in Love at First Kiss that was most frequently used was the Transposition Technique, namely 12 times (12.90%).